CIPP model evaluation of the impact of remuneration policies on lecturer performance in Indonesian state Islamic universities - Asy’ari, Hasyim; Komariah, Aan; Yuliana, Lia; Zahruddin; Silviani, Annisa; Vebrianto, Rian (Jurnal Cakrawala Pendidikan, 2025)
This study aims to evaluate the implementation of the remuneration policy and its impact on lecturer performance at State Islamic Universities in Indonesia. The policy, initiated by the central government as a form of recognition for lecturers' professionalism, is assessed using the CIPP (Context, Input, Process, Product) evaluation model. A qualitative approach was employed to comprehensively analyze the policy’s contextual background, resource allocation, implementation processes, and outcomes. Data was collected through document analysis and in-depth interviews with key mid-level stakeholders, including deans, members of the internal supervisory unit, the quality assurance team, the planning and finance bureau, the finance department, and the personnel bureau. The data were analyzed using a descriptive method involving data collection, reduction, display, and conclusion drawing. The findings indicate that the remuneration policy positively influences lecturers’ performance, particularly in fulfilling the three pillars of Indonesian higher education: education, research, and community service. This study provides valuable insights for university leaders and policymakers in enhancing the quality and effectiveness of remuneration policy implementation to support institutional advancement.